2021
DOI: 10.55563/clinexprheumatol/bz64na
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and outcome of thrombocytopenia in systemic lupus erythematous: single-centre cohort analysis

Abstract: Objectives: To characterize the frequency of thrombocytopenia in patients with SLE and determine its time of onset during the course of the disease, severity and impact on mortality. Methods:This was a single centre cohort analysis of 707 patients with SLE followed for up to 40 years. We reviewed the patients' clinical notes identifying the presence of thrombocytopenia, its time of onset and ascertained other clinical and serological features of the disease. Thrombocytopenia was classified as mild (100-149x10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 13 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…Thrombocytopenia is characterized by platelet counts below 100 × 10 9 /L and can be observed in 10%-40% of SLE patients. 7 , 8 Severe thrombocytopenia affects approximately 3%-20% of individuals with SLE and is often associated with a chronic disease course. 9 Thrombocytopenia can present as an initial clinical finding in approximately 5%-16% of patients with SLE.…”
Section: Epidemiology Of Thrombocytopeniamentioning
confidence: 99%
“…Thrombocytopenia is characterized by platelet counts below 100 × 10 9 /L and can be observed in 10%-40% of SLE patients. 7 , 8 Severe thrombocytopenia affects approximately 3%-20% of individuals with SLE and is often associated with a chronic disease course. 9 Thrombocytopenia can present as an initial clinical finding in approximately 5%-16% of patients with SLE.…”
Section: Epidemiology Of Thrombocytopeniamentioning
confidence: 99%
“…For the diagnosis of SLE, all studies except five [24][25][26][27][28] met the American College of Rheumatology (ACR) 1997/1982 [29,30] and/or Systemic Lupus International Collaborating Clinics (SLICC) 2012 [31] classification criteria for SLE or were based on clinical examination by a qualified physician or rheumatologist.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…ITP can occur before or during the course of SLE, and approximately 22.9% of SLE patients experience ITP before or after diagnosis. 1,2 Studies have shown that thrombocytopenia in SLE patients is associated with high disease activity, and severe thrombocytopenia at any point during the disease increases the risk of death. 1,2 Therefore, managing thrombocytopenia in SLE patients is crucial for improving their prognosis.…”
Section: Introductionmentioning
confidence: 99%